The Relationship Between Nocturia and Mortality: Data From the National Health and Nutrition Examination Survey - Moon, Shinje; Kim, Yoon Jung; Chung, Hye Soo; Yu, Jae Myung; Park, Il In; Park, Sung Gon; Pak, Sahyun; Kwon, Ohseong; Lee, Young Goo; Cho, Sung Tae (International neurourology journal, 2022)
Purpose: We investigated the relationship between nocturia and mortality risk in the United States.Methods: Data were obtained from the National Health and Nutrition Examination Survey 2005–2010. Mortality data were obtained by linking the primary database to death certificate data found in the National Death Index with mortality follow-up up to December 31, 2015. Nocturia was defined based on symptoms reported in the symptom questionnaire. We categorized patients into 2 groups: mild nocturia (2–3 voids/night) and moderate-to severe nocturia (≥4 voids/night). Multiple Cox regression analyses were performed with adjustment for confounding variables at the baseline survey.Results: This study included 9,892 adults (4,758 men, 5,134 women). Nocturia occurred in 3,314 individuals (33.5%). Nocturia was significantly associated with all-cause mortality (hazard ratio [HR], 1.23; 95% confidence interval [CI], 1.10–1.39) and cardiovascular disease (CVD) mortality (HR, 1.55; 95% CI, 1.19–2.01). Moreover, the mortality risk increased with increasing nocturia severity. Further analysis with propensity score matching showed that nocturia was still significantly associated with all-cause mortality and CVD mortality. In subgroup analysis according to sex, nocturia was significantly associated with allcause mortality and CVD mortality in men. In women, moderate-to-severe nocturia was significantly associated with allcause mortality and CVD mortality. In subgroup analysis according to cardio-metabolic diseases, nocturia was associated with CVD mortality in patients with diabetes mellitus, hypertension, dyslipidemia, or CVD at baseline. In subgroup analysis of patients without diabetes mellitus, hypertension or CVD, nocturia was significantly associated with all-cause mortality.Conclusions: Nocturia was significantly associated with mortality in men and women after adjusting for major confounding factors.